2021
DOI: 10.1097/md.0000000000026959
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of long non coding maternally expressed gene 3 in pediatric acute myeloid leukemia

Abstract: The purpose of this study was to evaluate the correlation of long non-coding RNA maternally expressed gene 3 (Lnc-MEG3) with disease features, treatment response, and survival in pediatric acute myeloid leukemia (AML) patients. Among 92 de novo pediatric AML patients (before treatment and after 1 course of induction) and 40 controls, bone marrow mononuclear cells were obtained. Then, Lnc-MEG3 expression was determined by reverse transcription quantitative polymerase chain reaction. After 1 course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…lnc-meg3 may be Biomarkers associated with acute myeloid leukemia ( 79 ). As a biomarker, NRC-MEG3 is useful for disease management, treatment optimization, and improved prognosis in pediatric AML ( 80 ) and cALL ( 81 ) patients. The low expression of circ-ITCH is substantially connected with the aggressive clinicopathological characteristics and poor prognosis of various malignancies, according to research by Xiao-Dong Sun and Da-Wei Sun et al ( 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…lnc-meg3 may be Biomarkers associated with acute myeloid leukemia ( 79 ). As a biomarker, NRC-MEG3 is useful for disease management, treatment optimization, and improved prognosis in pediatric AML ( 80 ) and cALL ( 81 ) patients. The low expression of circ-ITCH is substantially connected with the aggressive clinicopathological characteristics and poor prognosis of various malignancies, according to research by Xiao-Dong Sun and Da-Wei Sun et al ( 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…In AML, it was shown that increased expression of MEG3 is a reliable molecular marker of favorable prognosis, both in pediatric and adult patients. In adult de novo AML patients, high MEG3 expression was independent predictor for longer DFS and OS [128], while in pediatric de novo AML patients increased MEG expression was associated with prolonged OS [133,134]. High MEG3 expression in AML patients after induction therapy was also associated with better DFS and OS, indicating that it could be used as a marker for the prediction of therapy response.…”
Section: Lncrna Meg3mentioning
confidence: 98%
“…MEG3 downregulation has been observed in both clinical samples and cell lines of leukemia. A line of studies reported that in acute myeloid leukemia (AML), the expression of MEG3 was reduced in bone marrow samples, peripheral blood mononuclear cells (PBMCs), as well as cell lines [32][33][34][35][36][37][38][39]41,42,[53][54][55][56]. Acute promyelocytic leukemia (APL) is a unique subtype of AML characterized by specific genetic defects, typically involving the fusion gene PML/RARα [57].…”
Section: Meg3 Expression In Hematological Malignanciesmentioning
confidence: 99%